Dasar Keberlakuan Pasal 14 Angka 8 Akta Notaris Terhadap Pendirian Lembaga Bantuan Hukum Berbentuk Yayasan (International Forum of Researchers and Lecturers, 2024)
This study aims to determine and analyse the basis for the enactment of Article 14 Point 8 of the Notary Deed towards the establishment of the foundation. The research method used in this research is Normative with a Legislation approach (statue approach) and case approach. The results showed that the validity of Article 14 number 8 of the Notarial Deed on the Establishment of a Legal Aid Institution in the Form of a Foundation does not have strong legal force because there are no rules that prohibit the management from concurrently implementing activities as contained in article 14 number 8 of the Notarial Deed on the Establishment of a Legal Aid Institution in the Form of a Foundation.